Application of medical-nursing integrated model and PDCA management in Traditional Chinese Medicine nursing ward rounds for a patient with chronic obstructive pulmonary disease (PDCA模式下1例慢性阻塞性肺疾病患者的医护一体化中医护理查房) - SHI Minjie (石明杰); WANG Liangmin (王梁敏) (中西医结合护理)
This paper summarized the practice of medical-nursing integrated model and PDCA management in Traditional Chinese Medicine nursing ward rounds for a patient with chronic obstructive pulmonary disease(COPD). An integrated management team consisted of doctors and nurses was established, and PDCA management was adopted in Traditional Chinese Medicine nursing ward rounds for the patient. The aim of implementing medical-nursing integrated model and PDCA management is to provide patients with professional, comprehensive and effective high-quality TCM nursing services through integrated medical and nursing TCM nursing rounds. (本文总结PDCA模式下1例慢性阻塞性肺疾病患者的医护一体化中医护理查房经验。成立医护一体化管理小组, 实施PDCA管理模式, 通过医护一体化中医护理查房, 为患者提供专业、全面、有效的优质中医护理服务。)